Ir–Re alloy as a highly active catalyst for the hydrogenolysis of glycerol to 1, 3-propanediol. Issue 3 (4th December 2014) - Deng, Chenghao; Duan, Xuezhi; Zhou, Jinghong; Zhou, Xinggui; Yuan, Weikang; Scott, Susannah L.
Abstract : We report for the first time the synthesis of a Ir–Re alloy catalyst, which exhibits significantly improved activity in glycerol hydrogenolysis and enhanced resistance against particle sintering compared with a Ir–ReO x structured catalyst. Abstract : In this work, bimetallic Ir–Re catalysts supported on KIT-6 are prepared by tuning the thermal treatment procedures, i.e., conventional calcination and reduction (Ir–Re/KIT-6-CR) and modified direct reduction (Ir–Re/KIT-6-R) after impregnation of two metal precursors. The structure of both catalysts is intensively characterized by H2 -TPR, STEM-HAADF-EDX, XPS and CO-DRIFTS. Results indicate that an Ir–Re alloy forms on the KIT-6 support when direct reduction is employed, which exhibits excellent catalytic performance in hydrogenolysis of glycerol. The formation rate of 1, 3-propanediol over Ir–Re/KIT-6-R reaches 25.6 mol1, 3-PD molIr −1 h −1 at 63% glycerol conversion with the addition of amberlyst-15 under 8 MPa H2, 393 K and 20 wt% glycerol aqueous solution, almost twice that over Ir–Re/KIT-6-CR. It is revealed that Re species without prior calcination treatment could be fully reduced and therefore couple with Ir to form an Ir–Re alloy structure with enhanced resistance against particle aggregation, while the calcination and subsequent reduction leads to the formation of an Ir–ReO x structure since the rhenium oxide species generated during the calcination is difficult to be reduced.